2017
DOI: 10.1007/s00535-017-1323-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide, afferent sensory nerves, and antioxidative enzymes in the mechanism of protection mediated by tricarbonyldichlororuthenium(II) dimer and sodium hydrosulfide against aspirin-induced gastric damage

Abstract: Background Aspirin exerts side effects within the gastrointestinal tract. Hydrogen sulfide (H 2 S) and carbon monoxide (CO) have been implicated in gastroprotection but the mechanism of beneficial action of these gaseous mediators against aspirin-induced damage has not been fully studied. We determined the involvement of afferent sensory neurons, calcitonin-gene-related peptide (CGRP), lipid peroxidation, and nitric oxide (NO) biosynthesis in gastroprotection of H 2 S-releasing NaHS and CO-releasing tricarbony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 37 publications
4
42
0
Order By: Relevance
“…Indeed, co‐treatment of CORM‐2 with l ‐NNA, a non‐selective NOS inhibitor, reduced the rate of ulcer healing and increase in GBF evoked by this CO donor. This observation is in line with previously published evidence showing that the inhibition of NOS reduced the gastroprotective effect of CORM‐2 against aspirin‐induced injury (Magierowski et al ., ). Moreover, the peripheral antinociceptive effect of the HO/CO pathway and possibly its contribution to gastroprotection could be mediated by the activation of K ATP channels (Pereira de Ávila et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Indeed, co‐treatment of CORM‐2 with l ‐NNA, a non‐selective NOS inhibitor, reduced the rate of ulcer healing and increase in GBF evoked by this CO donor. This observation is in line with previously published evidence showing that the inhibition of NOS reduced the gastroprotective effect of CORM‐2 against aspirin‐induced injury (Magierowski et al ., ). Moreover, the peripheral antinociceptive effect of the HO/CO pathway and possibly its contribution to gastroprotection could be mediated by the activation of K ATP channels (Pereira de Ávila et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Our results correspond with previous studies, which revealed that IL‐1β, TNF‐α mRNA and HIF‐1α mRNA and protein expressions were down‐regulated in gastric mucosa pretreated with CORM‐2 and compromised by stress, the administration of alendronate or aspirin (Magierowski et al ., ; Magierowski et al ., ,b). Additionally, CORM‐2 protected the gastric mucosa against aspirin‐induced lesions, downregulating the protein expression of iNOS (Magierowski et al ., ). This indicates that CO releasing CORM‐2 activity in ulcer healing involves similar factors and mechanisms to those observed in CO‐mediated gastroprotection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…19 However, systemic drugs, repeatedly used over a long period of time, have potential side effects and may lead to the development of bacterial resistance and local inadequate drug concentrations in the periodontal tissue and gingival crevicular fluid. 24 The long-term use of aspirin may cause side effects in the gastrointestinal tract including hemorrhagic micro-bleeding and gastric erosion; 25,26 and low-dose and topical applications of aspirin to treat disease would be very promising. An aspirin-loaded chitosan nanoparticle has been prepared and used to demonstrate that aspirin can be slowly and controllably released from the composite particles in vitro.…”
Section: Introductionmentioning
confidence: 99%